1992
DOI: 10.1177/104420739200300104
|View full text |Cite
|
Sign up to set email alerts
|

Is Supported Employment Cost-Effective in Minnesota?

Abstract: This paper reports on the application of a benefit-cost accounting framework to evaluate the economic outcomes of supported employment in Minnesota. Data were collected on the costs and economic outcomes of 1,892 individuals being served in 11 supported-employment agencies offering programs in habilitation training, on-site employment, and community-based group and individual supported employment. From these data net benefits and benefit-cost ratios were estimated to explain possible efficiency effects resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…As has been noted by other authors (Lewis et al, 1992), costs of supported employment vary considerably within and between states. So it may be that results documented here do not coincide with what is transpiring elsewhere.…”
Section: Discussionmentioning
confidence: 75%
“…As has been noted by other authors (Lewis et al, 1992), costs of supported employment vary considerably within and between states. So it may be that results documented here do not coincide with what is transpiring elsewhere.…”
Section: Discussionmentioning
confidence: 75%
“…Further, Lewis et al (1992) found that costs of services for supported employment vary widely from agency to agency. Consequently, the results of this study may have been different had the data been gathered in another locale.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, the majority of the available literature is derived from data collected in either Illinois [8,10,19,20,26,29] or Virginia [12,13,31]. Numerous studies have identified variations in employment outcomes between states [2,18,25]. Therefore, previous studies conducted in one state may not be predictive of outcomes achieved by supported employees in other states or across the entire country.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has suggested that cost of supported employment fluctuates significantly across and within states [6,18]. However, there has yet to be a nationwide examination of cost-efficiency from the workers' perspective.…”
Section: Introductionmentioning
confidence: 99%